TIMP-2 inhibits metastasis and predicts prognosis of colorectal cancer via regulating MMP-9. Issue 1 (1st January 2019) - Wang, Weimin; Li, Dan; Xiang, Liangliang; Lv, Mengying; Tao, Li; Ni, Tengyang; Deng, Jianliang; Gu, Xiancheng; Masatara, Sunagawa; Liu, Yanqing; Zhou, Yan
ABSTRACT: Colorectal cancer has a common cause of morbidity and mortality. Therefore, it is urgent to detect reliable biomarkers to predict prognosis in CRC. Here, we determined the expression of TIMP-2 and MMP-9 in a CRC tissue microarray by immunohistochemistry. We found that lower TIMP-2 or/and higher MMP-9 expression in cancer tissues was correlated with poorer overall survival (OS). TIMP-2 or MMP-9 expression was independent prognostic factors for CRC. Furthermore, TIMP-2 and MMP-9 expression had a synergistic role as efficient prognostic indicators for CRC patients. In vitro and in vivo, TIMP-2 could inhibit HCT 116 cells invasion and migration by regulating MMP-9. In sum, a combined expression of TIMP-2 and MMP-9 as efficient prognostic indicators was found for the first time.